2021
DOI: 10.14411/eje.2021.030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the energy content of diets on the development and quality of the fat reserves of larvae and reproduction of adults of the black soldier fly, Hermetia illucens (Diptera: Stratiomyidae)

Abstract: Hermetia illucens is a sustainable and an increasingly bioeconomical source of nutrients for farm animals. It is still necessary, however, to improve our knowledge of the biological features of this species in order to maximize its use. The aims of this research were to evaluate the effect of the energy level of rearing diets on its body weight and fat-body reserves. The quantity and quality of the fats storred by the non-feeding stages of this insect and its reproductive performances were also studied. A cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 67 publications
(52 reference statements)
1
6
1
Order By: Relevance
“…The human error was excluded as an influencing factor as the standard error value maintained high at T2 and T3, as well as for the prepupae weight. From a nutritional point of view (lipid and protein content), the L3.5 dietary treatment is partially comparable to the ED 1 diet formulated by Georgescu et al 26 . Already at 10 days of age, the L3.5 larvae were smaller than ED 1 (0.105 mg and about 0.162 mg, respectively).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The human error was excluded as an influencing factor as the standard error value maintained high at T2 and T3, as well as for the prepupae weight. From a nutritional point of view (lipid and protein content), the L3.5 dietary treatment is partially comparable to the ED 1 diet formulated by Georgescu et al 26 . Already at 10 days of age, the L3.5 larvae were smaller than ED 1 (0.105 mg and about 0.162 mg, respectively).…”
Section: Discussionmentioning
confidence: 71%
“…In recent years, research has started to focus the attention on the BSF nutritional requirements determination. In particular, studies related to protein, energy and carbohydrate needs have recently been carried out 23 , 26 , 27 . The knowledge on BSF nutrient requirements is still limited, even if the great number of scientific papers published on its life cycle and its use as feed ingredient 28 – 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased number of eggs in the clutch is correlated with the increase in weight, the differences between the different categories of clutches being statistically supported (Table 1). Our previous research demonstrated that these aspects depend on different experimental factors and/or treatments applied in larval feeding [14,17]. Egg length and width increase gradually and constantly from one egg clutch category to another.…”
Section: Biometric Egg Parametersmentioning
confidence: 99%
“…The capacity of ovipositing the eggs [11] is of paramount importance. The insect can reproduce only once; after the adult fly emerges, the accumulated energy reserves support the metabolic requirements of mating and egg laying [12][13][14]. Females generally lay between 300 and 1000 eggs [10,11,15], but the eggs number may be higher depending on the larval rearing medium [16,17].…”
Section: Introductionmentioning
confidence: 99%